Alcohol consumption patterns in Thailand and their relationship with non-communicable disease. (December 2015) - Wakabayashi, Mami; McKetin, Rebecca; Banwell, Cathy; Yiengprugsawan, Vasoontara; Kelly, Matthew; Seubsman, Sam-ang; Iso, Hiroyasu; Sleigh, Adrian
Abstract Background Heavy alcohol consumption is an established risk factor for non-communicable diseases (NCDs) but few studies have investigated drinking and disease risk in middle income, non-western countries. We report on the relationship between alcohol consumption and NCDs in Thailand. Methods A nationwide cross sectional survey was conducted of 87, 151 Thai adult open university students aged 15 to 87 years (mean age 30.5 years) who were recruited into the Thai Cohort Study. Participants were categorized as never having drunk alcohol (n  = 22, 527), as being occasional drinkers who drank infrequently but heavily (4+ glasses/occasion - occasional heavy drinkers, n  = 24, 152) or drank infrequently and less heavily (<4 glasses/occasion - occasional light drinkers, n  = 26, 861). Current regular drinkers were subdivided into those who either drank heavily (4 + glasses per occasion - regular heavy drinkers, n  = 3, 675) or those who drank less (<4 glasses/occasion -regular light drinkers, n  = 490). There were 7, 548 ex-drinkers in the study. Outcomes were lifetime diagnoses of self-reported NCDs and obesity (body mass index ≥ 25). Results Most women were never drinkers (40 % among females) or occasional light drinkers (39 %), in contrast to men (11 % and 22 %, respectively). Alcohol consumption was associated with urban in-migration and other recognized risks for NCDs (sedentary lifestyle and poor diet). After adjustment for these factors the odds ratios (ORs) for several NCDs outcomes - high cholesterol, hypertension, and liver disease - were significantly elevated among both occasional heavy drinkers (1.2 to 1.5) and regular heavy drinkers (1.5 to 2.0) relative to never drinkers. Conclusions Heavy alcohol consumption of 4 or more glasses per occasion, even if the occasions were infrequent, was associated with elevated risk of NCDs in Thailand. These results highlight the need for strategies in Thailand to reduce the quantity of alcohol consumed to prevent alcohol-related disease. Thailand is fortunate that most of the female population is culturally protected from drinking and this national public good should be endorsed and supported.